8.1k views
2 votes
D -e/3d + e= e, for d​

1 Answer

6 votes

Answer:


\large\boxed{d=(e^2+e)/(1-3e)}

Explanation:


(d-e)/(3d+e)=e\\\\(d-e)/(3d+e)=(e)/(1)\qquad\text{cross multiply}\\\\(1)(d-e)=(e)(3d+e)\qquad\text{use the distributive property}\\\\d-e=3de+e^2\qquad\text{add}\ e\ \text{to both sides}\\\\d=3de+e+e^2\qquad\text{subtract}\ 3de\ \text{from both sides}\\\\d-3de=e^2+e\qquad\text{distribute}\\\\d(1-3e)=e^2+e\qquad\text{divide both sides by}\ (1-3e)\\\\d=(e^2+e)/(1-3e)

User Adrianvintu
by
5.2k points